On Highly D-Efficient Designs with Nonnegatively Correlated Observations - Krystyna Katulska; Lukasz Smaga (Revstat Statistical Journal, 2017)
In the most difficult case where the number of observations n ≡ 3 (mod 4), high D-efficiency of certain chemical balance weighing designs under completely symmetric covariance matrix of errors is shown. It is also proved that D-optimal design may depend on the values of the correlation coefficient.